Implementation of Clusters Utilizing Resources Through High-Performance Computing - Daffa Surya Mahardhika; Angga Setiyadi (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2024)
The growing data volumes due to technological advancements and digitalization challenge single computing systems in terms of scalability. These systems often struggle with increasing workloads, leading to reduced performance and processing limitations. Additionally, electronic waste (e-waste) is a rising concern, as many functional computers are underutilized, contributing to environmental issues. This study proposes the use of cluster computing and High-Performance Computing (HPC) as solutions. Cluster computing aggregates computational power across multiple nodes to enhance capacity, while HPC optimizes performance for tasks requiring extensive data processing. Through a systematic approach focused on implementing PelicanHPC, the research demonstrates that cluster computing and HPC improve scalability and performance, particularly in Virtual Machines (VMs), and promote more efficient resource management. These solutions also help reduce environmental impact and cost inefficiencies. However, tests reveal that cluster performance remains suboptimal compared to physical computers, primarily due to network and hardware limitations. Future improvements should focus on enhancing hardware, network infrastructure, and software optimization